Acknowledgement to Reviewers of the Philippine Engineering Journal - Staff, PEJ (Philippine Engineering Journal; Vol 41 No 2 (2020), 2020)
The PEJ sincerely appreciates the excellent reviews and gratefully recognizes the generous contribution of the following reviewers in our recent publications.